Psychological resilience in promoting mental health in nursing students: A scope review protocol (Research, Society and Development, 2023)
This study aims to identify the published data about the resilience levels of nursing students using the Wagnild and Young resilience scale, through a scope review. The review protocol was registered in the Open Science Framework DOI: https://doi.org/10.17605/OSF.IO/52RA3 platform and will follow the Joanna Briggs Institute method. The PCC strategy (Population, Concept, Context) will be used to define the research question and the inclusion and exclusion criteria. The database search and selection strategy will be developed in conjunction with a professional specialized in digital search strategy and will include several databases, such as Cumulative Index to Nursing and Allied Health Literature (CINAHL), National Library of Medicine (PubMed), SCOPUS, WEB OF SCIENCE, MEDLINE, EMBASE, Scientific Electronic Library Online (SCIELO) and Google Scholar. Descriptors and synonyms will be used according to the Descriptors in Health Sciences (DeCS) and Medical Subject Headings (MeSH). Two reviewers will screen the titles, abstracts and full texts, extract the relevant data and perform the analysis and descriptive synthesis of the results, presented in tables, images, diagrams, tables and narratives following the PRISMA-ScR checklist. It is expected that this review will map the evidence available in the literature on the levels of resilience of nursing students using the Wagnild and Young scale, providing a clear and objective view of the results.